In vitro evaluation of pediatric restorative materials on human dental pulp stem cells - (:unkn) unknown (My University, 2022)
This in vitro study aimed to compare the cellular viability of four different restorative materials on human dental pulp stem cells (hDPSCs). The necessary tissues of isolated hDPSCs were obtained from 10 impacted third molars of healthy individuals 19???25 years old undergoing surgical extraction. The effects of GC Fuji IX GP, GC EQUIA Forte, APA Glass Carbomer, and APA Esthetic Fill eluates on hDPSCs??? viability on the first, third, and seventh days were examined by flow cytometry using an Annexin V binding assay. The cell viability ratios differed significantly between the restorative material groups (p 0.05). When the rates of late apoptotic cells were compared between the groups, no significant difference was observed, except for with the control group, which had the lowest rate of late apoptotic cells (p < 0.001). However, there was a significant difference in necrotic cell ratios between groups and days (p < 0.001; p = 0.001). The lowest rates of necrotic cells were found in the control group and Glass Carbomer groups, while the rates of necrotic cells were similar among the other groups. Therefore, we concluded that APA Glass Carbomer presents the highest cellular viability among the materials.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Anatomi; Biyokimya; Histoloji-Embriyoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Temel Bilimler; Medicine; Health Sciences; Fundamental Medical Sciences; Human Anatomy; Biochemistry; Histology and Embryology; Life Sciences; Molecular Biology and Genetics; Natural Sciences; ANATOMİ VE MORFOLOJİ; Biyoloji ve Biyokimya; Yaşam Bilimleri (LIFE); HÜCRE BİYOLOJİSİ; Moleküler Biyoloji ve Genetik; ANATOMY & MORPHOLOGY; BIOLOGY & BIOCHEMISTRY; Life Sciences (LIFE); CELL BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Biyokimya (tıbbi); Moleküler Biyoloji; Hücre Biyolojisi; Biochemistry (medical); Anatomy; Molecular Biology; Cell Biology; Restorative material; Stem cell; Human dental pulp; Cell viability; Annexin V; GLASS-IONOMER CEMENTS; CYTOTOXICITY; FIBROBLASTS; FLUORIDE